Intestinal permeability, microbial translocation, changes in duodenal and fecal microbiota, and their associations with alcoholic liver disease progression in humans. Issue 1 (9th November 2020) - Maccioni, Luca; Gao, Bei; Leclercq, Sophie; Pirlot, Boris; Horsmans, Yves; De Timary, Philippe; Leclercq, Isabelle; Fouts, Derrick; Schnabl, Bernd; Stärkel, Peter
ABSTRACT: Background: Animal data suggest a role of the gut-liver axis in progression of alcoholic liver disease (ALD), but human data are scarce especially for early disease stages. Methods: We included patients with alcohol use disorder (AUD) who follow a rehabilitation program and matched healthy controls. We determined intestinal epithelial and vascular permeability (IP) (using urinary excretion of 51 Cr-EDTA, fecal albumin content, and immunohistochemistry in distal duodenal biopsies), epithelial damage (histology, serum iFABP, and intestinal gene expression), and microbial translocation (Gram – and Gram + serum markers by ELISA). Duodenal mucosa-associated microbiota and fecal microbiota were analyzed by 16 S rRNA sequencing. ALD was staged by Fibroscan® (liver stiffness, controlled attenuation parameter) in combination with serum AST, ALT, and CK18-M65. Results: Only a subset of AUD patients had increased 51 Cr-EDTA and fecal albumin together with disrupted tight junctions and vasculature expression of plasmalemma Vesicle-Associated Protein-1. The so-defined increased intestinal permeability was not related to changes of the duodenal microbiota or alterations of the intestinal epithelium but associated with compositional changes of the fecal microbiota. Leaky gut alone did not explain increased microbial translocation in AUD patients. By contrast, duodenal dysbiosis with a dominance shift toward specific potential pathogenic bacteria genera ( Streptococcus, Shuttleworthia, Rothia ), increased IP and elevated markers of microbial translocation characterized AUD patients with progressive ALD (steato-hepatitis, steato-fibrosis). Conclusion: Progressive ALD already at early disease stages is associated with duodenal mucosa-associated dysbiosis and elevated microbial translocation. Surprisingly, such modifications were not linked with increased IP. Rather, increased IP appears related to fecal microbiota dysbiosis.